HLA-DRB1 alleles in children with post-streptococcal acute glomerulonephritis - Bakr, AM; Mahmoud, LA; El-Chenawi, FA; Salah, AA (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">To investigate the association between HLA-DRB1 alleles and post-streptococcal acuteglomerulonephritis (PSAGN), 32 children withPSAGN and 380 healthy subjects from the samelocality were typed for DRB1alleles usingpolymerase chain-reverse hybridization technique.Patients with PSAGN have significantly increasedfrequency of both DRB1* 03011 (46.9 vs. 19.2% incontrols, P = 0.00025) and DRB1* 1105 (31.1 vs.15.6% in controls, P = 0.0097). However, aftercorrection of P values, only the difference for DRB1*03011 remains significant (P = 0.025). Their relativerisks are significantly high [3.71, confidence interval(Cl) = 1.8-7.8, and 3.57, Cl = 1.4-8.9 respectively].No significant differences in the frequency of bothalleles arc observed among patients with differentgrades of hypertension, proteinuria or hematuria. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: DRB1* 03011, and presumably 1105,alleles confer susceptibility to PSAGN. However theseverity of the disease is not determined by these twoalleles.